Maternal health status in tribal India: A 5-year intervention program and its outcome - Amit Sengupta; Mamata Sahoo; Asif Khan; Raziya Shaikh; Rukhsar Khan (Wolters Kluwer Medknow Publications, 2020)
Introduction: There is poor penetration of evidence-based maternal health care provided under national health programs in resource-poor underserved regions. A well-planned locally acceptable community-driven comprehensive health promotion strategy and quality health care delivery mechanism is necessary to improve the situation. Objective: The main objective was to find the gaps in the existing system and promote health literacy and health-seeking behavior. Methodology: 80,000 tribal population living in isolated conflict zone of Bastar district was covered for 5 years between 2012 and 2017. An integrated health-care plan was developed with community leaders, panchayat, and the local government to promote and provide quality evidence-based maternal health care. Available resources were mobilized and health technologies introduced. Results: Regular home visits, point of care diagnostics, identification of high-risk mothers and their timely referral, and behavioral change communication increased the trust of the community. It resulted in higher demand for evidence-based health interventions. The adolescent pregnancy rate (<19 years) reduced to 6.8% (2016) from 13.5% (2012). Hemoglobin level >9 g% (third trimester) improved. Supervised births and high-risk referrals increased from 19.5% (2014) to 58% (2017) and 8.5% (2014) to 13.1% (2017), respectively. Although significant improvement was noted, key indicators continued to remain below rural Bastar (National Family Health Survey-4). Conclusion: Promotion of existing good practices, behavior change, health technologies, and evidence-based emergency care improved the maternal health status of the secluded and underserved tribal community, but persistent effort is needed to enable women access the quality maternal health services provided under National Health Mission.